Adoption of Electronic Medical Records: A TOE Framework Analysis - Khasanah, Lina; Sania, Adnin; Mohammad, Maula Ismail (Procedia of Engineering and Life Science, 2024)
The implementation of digital technology in the global health sector has received strong support, with the adoption of Electronic Medical Records (EMR) becoming a primary focus in modernizing health systems to improve service quality. However, in Indonesia, 48.9% or 4,807 community health centers (Puskesmas) have not yet adopted EMR technology. Therefore, pre-implementation analysis is crucial to identify barriers and opportunities for success. The TOE (Technology-Organization-Environment) framework serves as an analytical model for technology adoption at the organizational level, capable of explaining the factors influencing the decision to adopt technological innovations.This study aims to develop a TOE instrument in Indonesian, adapted from previous research, and adjusted to the research context. The instrument is structured in the form of a questionnaire, tested for validity and reliability. The validity test results indicate that all questionnaire items are valid (r calculated > r table), while the reliability test shows a Cronbach’s Alpha value of 0.916, indicating that the instrument is reliable. This questionnaire can be used to analyze the factors influencing technology adoption in the implementation of EMR in health facilities and can serve as a basis for future research development